VOLUME PERDAGANGAN DAN PERUBAHAN HARGA SAHAM : ANALISIS BERDASARKAN JENIS INFORMASI - C. Erna Susilawati (Media Riset Bisnis & Manajemen, 2008)
Stock trading exists because there is a difference between trader's opinions about expected value and security which is generating by same information. Traders opinion and expectation are reflected in trade volume. Trade volume can be classified in two components, i.e. trade frequency and transaction volume. The purpose of the study is to analyze the impact of trade frequency and transactions volume through stock price change. The study also discusses the impact of public and private information through transaction frequency and transactions volume. We use 45 stocks from 15 industries which classified to 3 (three) types of portfolios according to each market capitalization. The results of this study shows that trade frequency have significant impact to stock price change and neither to transactions volume. This mean tharbade frequency have information (private information). It can be concluded that each trader in Indonesian Stock Exchange (IDX) hase relative same information about public information but not to that of private information.Keywords: Trade frequency, transaction volume, public information, private information.